Normothermic Ex Situ Heart Perfusion With the Organ Care System for Cardiac Transplantation: A Meta-analysis. Issue 9 (27th May 2022) - Langmuur, Sanne J.J.; Amesz, Jorik H.; Veen, Kevin M.; Bogers, Ad J.J.C.; Manintveld, Olivier C.; Taverne, Yannick J.H.J.
Abstract : Background: Heart transplantation (HTx) is, at present, the most effective therapy for end-stage heart failure patients; however, the number of patients on the waiting list is rising globally, further increasing the gap between demand and supply of donors for HTx. First studies using the Organ Care System (OCS) for normothermic machine perfusion show promising results yet are limited in sample size. This article presents a meta-analysis of heart donation either after brain death (OCS-DBD) or circulatory death (OCS-DCD) on using OCS versus static cold storage used for HTx. Methods: A systematic literature search was performed for articles discussing the use of normothermic ex situ heart perfusion in adult patients. Thirty-day survival outcomes were pooled, and odds ratios were calculated using random-effects models. Long-term survival was visualized with Kaplan-Meier curves, hazard ratios were calculated and pooled using fixed-effects models, and secondary outcomes were analyzed. Results: A total of 12 studies were included, with 741 patients undergoing HTx, of which 260 with the OCS (173 DBD and 87 DCD). No differences were found between the 3 groups for early and late survival outcomes or for secondary outcomes. Conclusions: OCS outcomes, for both DBD and DCD hearts, appeared similar as for static cold storage. Therefore, OCS is a safe and effective technique to enlarge the cardiac donor pool in both DBD and DCD, with additional benefits for long-distance transport and surgically complex procedures. Abstract :